Medieval Merchants and Money Essays in Honour of James L. Bolton - Davies, Matthew (IHR Conference Series, 2016)
This volume contains selected essays in celebration of the scholarship of the medieval historian Professor James L. Bolton. The essays address a number of different questions in medieval economic and social history, as the volume looks at the activities of merchants, their trade, legal interactions and identities, and on the importance of money and credit in the rural and urban economies. Other essays look more widely at patterns of immigration to London, trade and royal policy, and the role that merchants played in the Hundred Years War.